Nitrous oxide emission from full-scale municipal aerobic granular sludge. (15th June 2021) - van Dijk, Edward J.H.; van Loosdrecht, Mark C.M.; Pronk, Mario
Abstract: The nitrous oxides emission was measured over 7 months in the full-scale aerobic granular sludge plant in Dinxperlo, the Netherlands. Nitrous oxide concentrations were measured in the bulk liquid and the off-gas of the Nereda® reactor. Combined with the batch wise operation of the reactor, this gave a high information density and a better insight into N2 O emission in general. The average emission factor was 0.33% based on the total nitrogen concentration in the influent. The yearly average emission factor was estimated to be between 0.25% and 0.30%. The average emission factor is comparable to continuous activated sludge plants, using flocculent sludge, and it is low compared to other sequencing batch systems. The variability in the emission factor increased when the reactor temperature was below 14 °C, showing higher emission factors during the winter period. A change in the process control in the winter period reduced the variability, reducing the emission factors to a level comparable to the summer period. Different process control might be necessary at high and low temperatures to obtain a consistently low nitrous oxide emission. Rainy weather conditions lowered the emission factor, also in the dry weather flow batches following the rainy weather batches. This was attributed to the first flush from the sewer at the start of rainy weather conditions, resulting in a temporarily increased sludge loading. Graphical abstract: Image, graphical abstract